Makna Huruf ‘Āmilah (Huruf Tujarru Ism Wahid) Dan Pengaruhnya Dalam Kesimpulan Hukum Kitab Bulûghul Marām - Yasin, Agus; Rahmawati, Nuraeni; bin Zaid, Abdul Hafidz; Arifin, Muhammad Syamsul; Ainun, Iqlima Nurul (STIQ Amuntai, 2024)
Letters play a crucial role in learning nahwu (Arabic syntax) to understand Arabic grammar, particularly in meaning analysis. Previous studies, such as those by Al-Khatib, examined the role of prepositions (huruf jar) in Arabic syntax, while Al-Jundi explored how these letters affect the grammatical status of verbs and sentence meaning. This article analyzes the meanings of huruf al-‘amilah (governing letters) concerning those governing a single noun (huruf tujarru ism wahid) and their influence on legal conclusions in Bulughul Maraam: Bab Thaharah by Al-Hafidz Ibn Hajar Al-‘Asqolaani, a book containing hadiths on Islamic legal principles. The study aims to: 1) Identify the meanings of huruf ‘amilah in Bulughul Maraam: Bab Thaharah; and 2) Determine the influence of these meanings on legal conclusions in the book. Using a library research method with a descriptive approach, data was collected through documentation and analyzed through classification, content analysis, and conclusion. The results show that the letter